2002
DOI: 10.1046/j.0022-0477.2001.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between persistent eosinophilia and asthma in childhood is independent of atopic status

Abstract: Longitudinal eosinophil levels are linearly associated with chronic asthma in childhood, independent of atopy. The strong association between parental asthma and eosinophil status suggests that genetic background may be an important determinant of eosinophilic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 21 publications
6
45
0
Order By: Relevance
“…Parental asthma is associated with increased and persistent peripheral blood eosinophilia, which is a characterizing feature of the presence of a T H 2-mediated response and which may be responsible for chronic asthma and allergy. 34 Finally, our results confirm previous findings about the existence of a gender reversal during puberty caused by an increase in reported asthma in women and a decrease in men. It has been suggested that airway caliber, in addition to hormonal factors, could play an important role in explaining the different pattern of incidence in men and women.…”
Section: Discussionsupporting
confidence: 93%
“…Parental asthma is associated with increased and persistent peripheral blood eosinophilia, which is a characterizing feature of the presence of a T H 2-mediated response and which may be responsible for chronic asthma and allergy. 34 Finally, our results confirm previous findings about the existence of a gender reversal during puberty caused by an increase in reported asthma in women and a decrease in men. It has been suggested that airway caliber, in addition to hormonal factors, could play an important role in explaining the different pattern of incidence in men and women.…”
Section: Discussionsupporting
confidence: 93%
“…A different mechanism may be present in persistent wheezers, given their different prognoses. We (5,15,16) and others (17)(18)(19) have reported that children with persistent wheeze are more likely than transient early wheezers to have high serum IgE levels, eosinophilia, and skin test reactivity to local aeroallergens. Lowe and coworkers (20) showed that, regardless of the development of early respiratory symptoms, children with a strong family history of asthma who had become sensitized to local allergens had significantly lower specific airway conductance at age 3 yr compared with nonsensitized children.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Karakoc et al [20], eosinophilia was linked to persistent asthma independently of atopia during childhood. This finding suggests that there is a strong correlation between parental asthma and eosinophilia; thus, genetics can be an important determinant of the eosinophilic response [20]. In our study, higher serum IgE levels and eosinophil counts were detected in the wheezing group compared to controls, although this finding was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%